Предмет: Математика,
автор: seregenkoilya2008
0.3х-(2,6-0,9х)=1,2х+3 пожалуйсто!!!)
Ответы
Автор ответа:
3
Пошаговое объяснение:
0,3х-(2,6-0,9х)=1,2х+3
0,3х-2,6+0,9х=1,2х+3
0,3х+0,9х-1,2х=3+2,6
1,2х-1,2х=5,6
0х=5,6
х=5,6:0 — уравнение решений не имеет, так как на 0 делить нельзя
Ответ: нет решений
Похожие вопросы
Предмет: Физика,
автор: KathyK
Предмет: Английский язык,
автор: ckrebenkova2002
Предмет: Математика,
автор: BELKA456
Предмет: Физика,
автор: Карина12121212
Предмет: Математика,
автор: marinakalimova
0.3х+1.8=0.4х-2.6
0.4х-0.3х=1.8+2.6
0.1х=4.4
х=4.4÷0.1
х=44